THE HINDRANCES OF PARENTAL SUPPORT IN ENHANCING THE ACADEMIC PERFORMANCE OF GRADE 9 LEARNERS IN A SECONDARY SCHOOL. - Msibi, Ntombifuthi Innocentia; Maseko, Nonhlanhla Desiree (IJIET (International Journal of Indonesian Education and Teaching), 2025)
The study focuses on parental involvement and its impact on the academic performance of grade nine learners in Bronkhorstspruit, Gauteng province. It highlights that many parents in the area tend to defer responsibility for their children's academic success solely to educators, expecting schools to address any challenges. This reliance is compounded by low attendance at parent meetings and minimal participation in school activities. Consequently, academic performance suffers among grade nine learners in the region. The research aims to offer effective strategies for parents to enhance their children's academic outcomes and to advise schools on fostering better parental involvement. Following a qualitative approach within the Interpretivism paradigm, data was gathered through semi-structured interviews and document analysis involving ten purposefully selected parents, though only five participated. The study is theoretically grounded in the Hoover-Dempsey Sandler Model of Parental Involvement, which explores parental motivations and perceptions regarding involvement in their children's education. Key findings indicate that issues such as parental knowledge gaps and strained relationships between schools and parents contribute significantly to the lack of parental support in Bronkhorstspruit schools.